Biofilm formation of Listeria monocytogenes in hydroponic and soil grown lettuce leaf extracts on stainless steel coupons. (May 2020) - Kyere, Emmanuel O.; Foong, Grace; Palmer, Jon; Wargent, Jason J.; Fletcher, Graham C.; Flint, Steve
Abstract: Foodborne outbreaks associated with fresh produce due to human pathogenic bacteria have become a global concern. In this study, we investigated the ability of three fresh produce associated L. monocytogenes strains: PFR O8A06 (coleslaw isolate), PFR O8A07 and O8A08 (cabbage isolates) to survive and form biofilms on stainless steel coupons in extracts of lettuce leaves obtained from soil and hydroponic systems at 4 °C and 10 °C. There was no significant difference (p < 0.05) between the hydroponic and soil grown leaf extracts in terms of L. monocytogenes survival, growth and biofilm formation. The biofilm formation of L. monocytogenes on stainless steel for both soil and hydroponic leaf extracts at 10 °C increased from 3 log to 6.4–7.2 log CFU/cm 2 . At 4 °C, the biofilm formation of all three strains for both soil and hydroponic leaf extracts increased to 4.3–4.8 log CFU/cm 2 . These findings suggest that lettuce leaf extracts support the survival, growth and biofilm formation of L . monocytogenes on stainless steel irrespective of the growth system used and this might be a potential cause for recurring contamination in the processing environment. Highlights: Lettuce leaf extracts support biofilm growth of L. monocytogenes on stainless steel. L. monocytogenes shows similar growth in both hydroponic and soil grown lettuce extract. L. monocytogenes shows similar biofilm formation on stainless steel in both soil and hydroponic lettuce extract.